I‘JĀZ AL-QUR’AN DALAM PERSPEKTIF MANA’ KHALIL AL-QATTAN - Adib Fattah Suntoro; amir sahidin (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2022)
The Qur'an as Kalāmullah is the greatest miracle that was revealed to the prophet Muhammad SAW to be used as a guide for all human life until the Day of Judgment. Therefore, Allah instituted a debilitating or i'jāz character by which he would reveal the incompetence of his opponents. However, from the time of the prophet until now, there have been opponents of the Qur'an or people who doubt its authenticity. For this reason, the scholars are very attentive in discussing the i'jāz al-Qur'an, among those who pay serious attention to this study is Mana' Khalil al-Qattan. Through research that is library research, it can be concluded that, according to Mana' Khalil al-Qattan, the miracles of the Qur'an lie in all its aspects, such as language, sharia, scientific values ​​and so on. While the level of miracles of the Qur'an is comprehensive, even if it is a single letter. In addition, al-Qattan highlights the three most important aspects of i'jāz al-Qur'an, namely i'jāz al-lughawy, al-i'jāz al-ilmy, and al-i'jāz al-tasyrī'i which will always exist forever.